Knowledge and perceptions regarding Human Papillomavirus (HPV) and willingness to receive HPV vaccination among university students in a north-eastern city in Turkey - Ceren Varer Akpinar; Sebnem Alanya Tosun (BMC, 2023)
Abstract Background For a HPV vaccination program to be successful, it is important that the target population has sufficient knowledge about HPV and HPV vaccines. The aim of this study was to evaluate HPV-related knowledge levels among students at a university in northern Turkey, to assess vaccination willingness, and to determine factors associated with HPV-related knowledge. Methods This cross-sectional study was conducted on 824 (93.1%) students studying at 16 different faculties. The study population was identified through the proportional stratified sampling method. Data were collected through a questionnaire including socio-demographic characteristics and the HPV Knowledge Scale. Multiple linear regression analysis was performed to identify factors that may be associated with knowledge scores. Results 43.6% of the students had never heard of HPV, 50.6% of them had never heard of HPV screening tests or HPV vaccination. Only 2.7% of the students were vaccinated against HPV and 15.7% were willing to receive HPV vaccination. Awareness of HPV and willingness to receive vaccination were found to be higher among women, while previous experience with sexual intercourse was higher in men (p < 0.05). The mean HPV knowledge score was quite low (6.74 ± 7.13 out of 29 points). The studying in a field related to health sciences, being a senior student, intending to be vaccinated, being a woman, having had sex were found to be associated with high knowledge levels (p < 0.05). Conclusions Educational programmes should be developed to increase university students' knowledge about HPV and the HPV vaccine.